2014
DOI: 10.1038/ncb2920
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microtubule motors by tubulin isotypes and post-translational modifications

Abstract: The ‘tubulin-code’ hypothesis proposes that different tubulin genes or posttranslational modifications (PTMs), which mainly confer variation in the carboxy-terminal tail (CTT), result in unique interactions with microtubule-associated proteins for specific cellular functions. However, the inability to isolate distinct and homogenous tubulin species has hindered biochemical testing of this hypothesis. Here, we have engineered 25 α/β tubulin heterodimers with distinct CTTs and PTMs and tested their interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
543
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(570 citation statements)
references
References 64 publications
25
543
1
1
Order By: Relevance
“…The CTT are also a major focus of post-translational modifications that comprise the "tubulin code" (8). In the microtubule, these tails form a charged brush surrounding the microtubule (9 -12) and, in this context, the post-translational modifications are recognized to regulate binding of other proteins (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CTT are also a major focus of post-translational modifications that comprise the "tubulin code" (8). In the microtubule, these tails form a charged brush surrounding the microtubule (9 -12) and, in this context, the post-translational modifications are recognized to regulate binding of other proteins (13).…”
Section: Resultsmentioning
confidence: 99%
“…This evolutionarily ancient post-translational modification of tubulin is usually related to microtubule stability and binding of other proteins to the microtubule (13), although also implicated in rapid shifts during cellular signaling (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Microtubule motors, including cytoplasmic dynein and kinesin-5, move along microtubules by interacting with tubulins (47,(55)(56)(57). There are two basic types of microtubule motors: plus-end motors and minus-end motors, depending on the direction in which they move along the microtubule track within the cell.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, kinesin-1 has been reported to prefer stable (acetylated/detyrosinated) MTs (Dunn et al 2008;Konishi and Setou 2009;Reed et al 2006). Additional in vitro studies showed that kinesin-1 motility is increased by polyglutamylation and that detyrosination of α-tubulin promotes kinesin-2 motility (Sirajuddin et al 2014). It has been hypothesized that posttranslational modifications, together with specific MAP patterns, form a "tubulin code" that can be "read" by factors that interact with MTs, such as motor proteins (Janke and Bulinski 2011;Tischfield and Engle 2010;Verhey and Gaertig 2007).…”
Section: Organization Of Axonal and Dendritic Microtubulesmentioning
confidence: 99%